Li2CO3/LiF‐Rich Heterostructured Solid Electrolyte Interphase with Superior Lithiophilic and Li+‐Transferred Characteristics via Adjusting Electrolyte Additives. Issue 18 (23rd March 2022) - Wu, Daxiong; He, Jian; Liu, Jiandong; Wu, Mingguang; Qi, Shihan; Wang, Huaping; Huang, Junda; Li, Fang; Tang, Dongliang; Ma, Jianmin
Abstract: The structure and components of solid electrolyte interphase (SEI) is crucial to direct the growth of lithium particles. However, it is hard to have control over them. Herein, an SEI that shares the properties of Li2 CO3 ‐rich and LiF‐rich types is realized by using different fluorine phenylphospines, and constructing a Li2 CO3 /LiF‐rich heterostructured SEI by using tris(4‐fluorophenyl)phosphine (TFPP) as the electrolyte additive. The well‐balanced SEI formed in TFPP‐containing electrolyte has the fast Li + transport kinetics of Li2 CO3, good electron insulator capability of LiF, and strong affinity toward Li + . It can effectively guarantee fast, uniform Li + flux through the SEI while preventing electrons from the Li anode entering into SEI, and thus realizes uniform and dense Li deposition at the SEI/Li interface. As expected, the Li anode with TFPP‐containing electrolyte achieves a stable Li plating/stripping over 400 h at 1mA cm −2 while the full cell with a high‐voltage LiNi0.6 Co0.2 Mn0.2 O2 cathode also enables long‐term stability with a capacity retention (87.8% after 200 cycles) at 0.1 A g −1 and excellent rate performance. Abstract : A tris(4‐fluorophenyl)phosphine‐containing electrolyte endows a LiF/Li2 CO3 ‐rich heterostructured solid electrolyte interphase with the fast Li + transport kinetics of Li2 CO3, the good electron insulator capability of LiF, and a strong affinity toward Li + .